Lack of trust or no trust strategy? The relations between the commune authorities and town authorities in Zielona Góra in the process of merging the two administrative bodies = Brak zaufania czy strategia braku zaufania? Relacje władz gminy i miasta Zielona Góra w procesie łączenia samorządów - Lisowski, Krzysztof (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The article is the attempt to describe the process of merging the two administrative bodies of city and communes governments units. In the first part I established the base for public process which was created for integration of self-government bodies. I characterized also relations of city and commune authorities before the appearance of the project to merge. While searching for the answers for the question put in the title of the article, I referred to the public debate (texts placed in the local media). The analysis showed the large lack of the trust of commune authorities in comparison with municipal authorities, which did not result from the levering of essential recordings of the prepared social contract but from lack of belief in their constancy and realization. Such manner was called the strategy of the distrust.
Keywords: zgodne łączenie samorządów; strategia braku zaufania; dyskurs publiczny; suburbanizacja; succesful consensual merge of local governments units; the strategy of lack; distrust; public debate; suburbanization